The Implications of Post-Pandemic Religious Life Through the Indonesian Ulema Council Fatwa Concerning Covid-19: A Case Study of the Moslem Community in Makassar - Achmad Musyahid; Halim Bahri Darwis; Sulfianti Sulfianti (MUI Sulawesi Selatan, 2022)
This study examined the conditions of religious life in Manggala District during and after the pandemic, especially in worship, as well as the community’s response to the fatwa issued by the Indonesian Ulema Council concerning Covid-19. A qualitative field study was adopted with an interview technique. The primary data were interviews with the Manggala District community, and the secondary included literature, books, journals, and scientific works related to this study. The results showed that the condition of the Manggala District community during Covid-19 in religious matters was significantly impacted and underwent drastic changes, including the implementation of Friday and congregational prayers and the non-observance of Eid al-Fitr and Eid prayers. The worship condition of the people after the pandemic was operating properly and could be implemented as stipulated in Islamic law. Furthermore, there were differences in attitudes among the community. Some agreed, and others disagreed with the issuance of the MUI fatwa on Covid-19 according to their respective reasons.